1974
DOI: 10.1055/s-0028-1095709
|View full text |Cite
|
Sign up to set email alerts
|

Free Triiodothyronine (T3)- and Thyroxine (T4) Serum Levels in Old Age

Abstract: Free Triiodothyronine (T3)-and Thyroxine (T4) Serum Levels in Old Age 239 Due to the ubiquitous distribution of adipose tissue and the substantial insulin degrading activity observed, it would appear that this tissue may play an important role in insulin turnover in the body. References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
1
2

Year Published

1979
1979
2002
2002

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 0 publications
1
14
1
2
Order By: Relevance
“…There are reports (5,17) show-ing a decrease in T4 and T31evels and their corresponding free hormone indices in a group of aging men (30-96 years). On the other hand, most studies have not revealed any significant decrease in serum T4 with age (6,8,13). Controlling for age in the multiple regression analyses did not affect the relationship between duration of lead exposure and FT4 or T41evel in the present study.…”
Section: Discussioncontrasting
confidence: 66%
“…There are reports (5,17) show-ing a decrease in T4 and T31evels and their corresponding free hormone indices in a group of aging men (30-96 years). On the other hand, most studies have not revealed any significant decrease in serum T4 with age (6,8,13). Controlling for age in the multiple regression analyses did not affect the relationship between duration of lead exposure and FT4 or T41evel in the present study.…”
Section: Discussioncontrasting
confidence: 66%
“…Com relação aos níveis séricos de T3, vários estudos demonstraram uma diminuição progressiva com a idade (9,18,19,23,25,26), chegando a 5,1ng/dl por década (25), embora o T3 reverso não tenha mostrado a mesma tendência (23,26). Por outro lado, outros trabalhos não confirmaram esta tendência na queda do T3 em função da idade (14,24,27).…”
Section: Nívei Dos Hormônios Tiroideanos Tsh E Tbgunclassified
“…Alguns autores concordam que, com a idade, ocorra uma diminuição dos níveis séricos de T3, T4 e FT4 (9,14,(18)(19)(20)(21)(22)(23)25,26), enquanto para outros estes se mantém inalterados (14,23,24,27) com o envelhecimento. Níveis elevados (4,8,14) de TSH, baixos (15)(16)(17) ou inalterados (18) já foram descritos na população idosa.…”
Section: Introductionunclassified
“…Both Herrmann et (1974) and Hansen et (1975) have reported similar findings of T-3 values with age. Rubenstein et (1973) attri bute the decrease in T-3 with age to three possible causes: (1) a de crease in the amount of T-3 secreted by the thyroid; (2) a change in the rate in which T-4 is deiodinated to T-3 by peripheral tissues; (3) an in crease in the utilization of T-3 as compared to that of T-4.…”
mentioning
confidence: 52%
“…They stated that this may be due to a decrease in the concentration of the thyroxine binding globulins which are estrogen dependent. Herrmann et (1974) reported a decrease in thyroxine concentra tions from 7.8 ug/100 ml, in a group 20-64 years old, to 6.4 yg/100 ml, in a group 65-92 years old.…”
mentioning
confidence: 91%